2022
DOI: 10.3390/polym14204289
|View full text |Cite
|
Sign up to set email alerts
|

Improved Flexural Properties of Experimental Resin Composites Functionalized with a Customized Low-Sodium Bioactive Glass

Abstract: This study evaluated the flexural properties of an experimental composite series functionalized with 5–40 wt% of a low-Na F-containing bioactive glass (F-series) and compared it to another experimental composite series containing the same amounts of the conventional bioactive glass 45S5 (C-series). Flexural strength and modulus were evaluated using a three-point bending test. Degree of conversion was measured using Fourier-transform infrared spectroscopy. Weibull analysis was performed to evaluate material rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Instead, the improvement is likely caused indirectly due to the ability of the customized BG to improve the degree of conversion of the polymer matrix compared to the Control material. This aspect was investigated in a previous study, which showed that the degree of conversion was reduced from 67.4% measured for the Control composite to 63.7% when 40 wt% BG 45S5 was added but improved to 71.6% when 40 wt% of the customized BG was added [ 20 ]. In that study, [ 20 ], an improved degree of conversion resulted in improved macro-mechanical properties (flexural strength and modulus), while in the present study, an analogous effect was observed on micromechanical properties (microhardness).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the improvement is likely caused indirectly due to the ability of the customized BG to improve the degree of conversion of the polymer matrix compared to the Control material. This aspect was investigated in a previous study, which showed that the degree of conversion was reduced from 67.4% measured for the Control composite to 63.7% when 40 wt% BG 45S5 was added but improved to 71.6% when 40 wt% of the customized BG was added [ 20 ]. In that study, [ 20 ], an improved degree of conversion resulted in improved macro-mechanical properties (flexural strength and modulus), while in the present study, an analogous effect was observed on micromechanical properties (microhardness).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the drawbacks associated with the high reactivity of BG 45S5, a less reactive, low-Na F-containing BG was formulated and investigated as a functional filler for resin composites. In previous studies with experimental composites functionalized with this low-Na F-containing BG, positive results were obtained for the following properties: acid neutralization [ 17 ], degree of conversion and polymerization kinetics [ 18 ], polymerization shrinkage properties [ 19 ], flexural properties [ 20 ], ion release [ 21 ], and the resulting anti-demineralizing protective effect on enamel [ 22 ] and dentin [ 23 ]. The aim of the present study was to complement these investigations by evaluating properties related to the exposure of composite materials to water, namely microhardness, mass changes during long-term immersion, water sorption and solubility evaluated according to ISO 4049, and surface precipitation of calcium phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Flexural strength and modulus were appraised using a three-point bending test and WA was done to estimate material reliability. A higher Weibull modulus of 5.0 was obtained, signifying that the material is reliable for the intended applications [ 330 ].…”
Section: Overview Of Weibull Analysis (Wa)mentioning
confidence: 99%
“…Revisiting the research conducted in the field of optimizing the properties of dental polymers, there are many interesting reports. In other words, many fillers have been used to improve the properties of dental polymers, some of which are polyacrylonitrile (PAN) nanofibers [ 2 ], carbon nanotubes modified by silane coupling agents [ 3 ], Ag nanoparticles [ 4 ], quaternary ammonium polyethylenimine nanoparticles (QA-PEI-NPs) [ 5 ], bioactive glass [ 6 ], SiO 2 nanofibers [ 7 ], alumina particles [ 8 ], spherical silica [ 9 ], hydroxyapatite whisker [ 10 ], nano fibrillar silicate [ 11 ], nano-zirconia fillers [ 12 ], electrospun nano-scaled glass fiber [ 13 ], NaF-loaded core–shell PAN–PMMA nanofibers [ 14 ], and APTES- or MPTS-conditioned nanozirconia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%